3,3′-[1,2-Phenylenebis(methylene)]bis(1-ethylbenzimidazolium) dibromide - Haque, Rosenani A. (International Union of Crystallography, 2012)
In the title molecular salt, C(26)H(28)N(4) (2+)·2Br(−), the central benzene ring makes dihedral angles of 76.75 (11) and 82.40 (10)° with the pendant benzimidazole rings. The corresponding angle between the benzimidazole rings is 57.03 (9)°. In the crystal, the cations and anions are linked via C—H⋯Br hydrogen bonds, forming sheets lying parallel to the bc plane. The crystal structure also features weak C—H⋯π interactions.